2012
DOI: 10.14746/ssllt.2012.2.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Ego boundaries and attainments in FL pronunciation

Abstract: The paper reports on a study designed to examine the relationship between the thickness of ego boundaries and attainments in FL pronunciation after a clearly structured form-focused practical course of phonetics. The research involved 45 first-year students of the Institute of English Studies in Wroclaw, Poland, who had attended around thirty 90-minute classes in phonetics. To measure the thickness of their ego boundaries, the Hartmann Boundary Questionnaire (HBQ) was administered. This permitted an examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The student who is aware of, but not threatened by, linguistic differentiation, and who treats it as an occasion for introspection, experimentation and, ultimately, learning, is the one for whom tolerance of ambiguity will be a help, not a hindrance” (p. 93). This was confirmed in Baran-Lucarz's (2012) study on types of ego boundaries and accuracy in English L2 pronunciation. She found a weak positive correlation between pronunciation scores and a boundary representing “the subjects’ attitudes towards accepting objects, concepts and situations that lack clear borders” (p. 60).…”
Section: Literature Reviewsupporting
confidence: 60%
“…The student who is aware of, but not threatened by, linguistic differentiation, and who treats it as an occasion for introspection, experimentation and, ultimately, learning, is the one for whom tolerance of ambiguity will be a help, not a hindrance” (p. 93). This was confirmed in Baran-Lucarz's (2012) study on types of ego boundaries and accuracy in English L2 pronunciation. She found a weak positive correlation between pronunciation scores and a boundary representing “the subjects’ attitudes towards accepting objects, concepts and situations that lack clear borders” (p. 60).…”
Section: Literature Reviewsupporting
confidence: 60%
“…Some research has been carried out to see whether ego boundaries, that is, subjective inhibitions, can be weakened through consumption of alcohol or Valium (Guiora, Acton, Erard, & Strickland, 1980;Guiora, BeitHallahmi, et al, 1972). Baran-Lucarz (2012) investigated the link between types of ego boundaries and accuracy in L2 pronunciation. She found few relationships but a weak positive correlation ermerged between pronunciation scores and a boundary representing ''the subjects' attitudes towards accepting objects, concepts and situations that lack clear borders'' (p. 60).…”
Section: Research On Empathymentioning
confidence: 99%
“…Many studies (Baran-Łucarz, 2011; Derwing & Rossiter, 2002;Horwitz et al, 1986;Kitano, 2001;Szyszka, 2011) have shown that anxiety the major constituent of Neuroticismhas a negative influence on the process of pronunciation learning and the level reached by L2 learners. Baran-Łucarz (2012) has also found important links between various dimensions of ego boundaries and pronunciation accuracy in the case of a formal setting with explicit PfI.…”
Section: Personality and Fl Pronunciation-related Attainmentreview Of...mentioning
confidence: 96%